2023
DOI: 10.2131/jts.48.139
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine protects against Ropivacaine-induced neuronal pyroptosis via the Nrf2/HO-1 pathway

Abstract: Dexmedetomidine (DEX) has been demonstrated to protect against ropivacaine (Ropi)induced neuronal damages. This study was conducted to explore the protective role of DEX in Ropiinduced neuronal pyroptosis and provide a strategy to eliminate Ropi-induced neurotoxicity. The impacts of different concentrations of Ropi and DEX on neurotoxicity in SK-N-SH cells were evaluated by cell counting kit-8 assay and lactic dehydrogenase assay kits. Levels of nuclear factor erythroid 2-related factor 2 (Nrf2), heme oxygenas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Metformin can increase p38 MAPK activity, thereby helping reduce inflammation. 13,14 Oxidative stress, caused by an imbalance between free radicals and antioxidants, can cause nerve cell damage and increase inflammation. Metformin can help reduce oxidative stress by increasing antioxidant enzyme activity and scavenging free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin can increase p38 MAPK activity, thereby helping reduce inflammation. 13,14 Oxidative stress, caused by an imbalance between free radicals and antioxidants, can cause nerve cell damage and increase inflammation. Metformin can help reduce oxidative stress by increasing antioxidant enzyme activity and scavenging free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…We conjecture there may be the following reasons: 1) The duration of MCD-diet feeding was too short to reach a certain degree of disease severity; 2) The expression level of Sirt1 may be more related to the stage of fibrosis in NASH, but no fibrosis was observed in our models; 3) Differences in gene expression exist between human and mouse. Despite the research on the action of SIRT1 on ferroptosis in liver disease is limited, it has been indicated that ulinastatin can protect against acetaminophen-induced liver damage by minimizing ferroptosis via activating the SIRT1/NRF2/HO-1 pathway ( 46 ). Intriguingly, resveratrol, a potent SIRT1 activator, modulates FOXO1 deacetylation and thus resists iron overload-induced liver tissue damage in iron overload mouse models ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…By amplifying inflammatory responses and recalling innate immune cells, pyroptosis could be triggered and enhanced in the TME to attract and activate inflammatory cells. Wang et al [170] demonstrated that chemotherapy drugs induce pyroptosis in cancer cells in vitro, mediated by caspase-3 activation and the subsequent cleavage of GSDME. Gao et al [171] conducted the most detailed study on the role of pyroptotic cell death in CCA.…”
Section: Possible Therapeutical Approachesmentioning
confidence: 99%